2011
DOI: 10.1007/s00508-011-0035-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of unilateral headaches beyond migraine and cluster headache and their response to indomethacin

Abstract: The majority of previous studies on unilateral headaches beyond migraine and cluster headache have focussed on certain disorders such as paroxysmal hemicrania, SUNCT and primary stabbing headache. We assessed headache characteristics, importance of neuroimaging and response to indomethacin in an unselected series of uncommon unilateral headaches. We investigated all consecutive patients presented with unilateral headaches not fulfilling ICHD-II criteria of migraine and cluster headache. Patients underwent cran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…Depression and anxiety disorders represent undisputable co-factors in the progression of CH and require adequate treatment [ 16 ]. Other brain conditions, mainly vascular, should be carefully ruled out by appropriate investigation, including the carotid dissection [ 17 - 19 ]. CCH sufferers often overuse symptomatic medications to treat CH attacks and may develop medication overuse headache (MOH) in addition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depression and anxiety disorders represent undisputable co-factors in the progression of CH and require adequate treatment [ 16 ]. Other brain conditions, mainly vascular, should be carefully ruled out by appropriate investigation, including the carotid dissection [ 17 - 19 ]. CCH sufferers often overuse symptomatic medications to treat CH attacks and may develop medication overuse headache (MOH) in addition.…”
Section: Discussionmentioning
confidence: 99%
“…Behaviours exaggerating CH attacks like alcohol consumption, smoking, taking naps, vasodilating antihypertensives should be avoided [ 21 ]. The indomethacin test is recommended to exclude paroxysmal hemicrania, since there are cases with overlapping clinical pictures [ 17 , 22 ]. Investigation with polysomnography may be useful to exclude several rare conditions that may exaggerate CCH [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that PH is probably more common than it was anticipated earlier. Seidel et al [11] reported 63 consecutive patients with unilateral headache not resembling migraine or CH. Only twenty-four patients received a diagnosis of primary headache disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of clear cut biological marker, it will be difficult to differentiate borderline or atypical cases of TACs and HC. In Seidel et al [11] case series of 63 consecutive patients with unilateral headache not resembling migraine or CH, only twenty-four patients (38%) received a diagnosis of primary headache disorders. Headaches could not be classified according to present ICHD-II criteria in 49% patients.…”
Section: Discussionmentioning
confidence: 99%
“…We read with great interest the recent discussion of our paper by Drs. Taylor, Kaniecki, and Landy 1 . We agree that the current International Classification of Headache Disorders 2nd Edition (ICHD‐II) criteria for hemicrania continua (HC) are too strict.…”
mentioning
confidence: 78%